2020
DOI: 10.1111/ijcp.13738
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D level in a sample of Egyptian females of childbearing age attending a family medicine center

Abstract: Background Vitamin D deficiency is now recognised as a pandemic. The normal range of Vitamin D in the Arab countries is much lower than the international standards. Several Arab countries have published studies assessing serum Vitamin D levels among women––to date there is no national study assessing Vitamin D levels among Egyptian women. Objective The aim of the study is to measure Vitamin D level among Egyptian women of childbearing age. Patients and Methods We included 100 healthy adult females of childbear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…These observations suggest that there may not be an efficient transfer of 25(OH)D to the newborn or that there is an independent regulation of 25(OH)D in the mother and the newborn [ 38 , 39 ]. These observations between sufficient maternal 25(OH)D levels and deficient newborn 25(OH)D levels have been reported in several studies [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 78%
“…These observations suggest that there may not be an efficient transfer of 25(OH)D to the newborn or that there is an independent regulation of 25(OH)D in the mother and the newborn [ 38 , 39 ]. These observations between sufficient maternal 25(OH)D levels and deficient newborn 25(OH)D levels have been reported in several studies [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, other studies demonstrated that there was no significant difference in serum vitamin D level in RA and controls [27,28]. Vitamin D deficiency was present in almost all Egyptian healthy adolescents [29] and prevalent among Egyptian women of childbearing age [30]. There was a significant association between lack of physical activity, sun exposure, and vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 69%
“…An observational study conducted in Pakistan reported that an inadequate vitamin D status is common among women of childbearing age [ 51 ]. Another observational study found that 56% of Egyptian women of childbearing age had a vitamin D deficiency or insufficiency [ 52 ]. Looking at results from countries other than those with an income level similar to Brazil, we found an observational study conducted in Sweden reporting that more than a third of pregnant women had low levels of 25-hydroxyvitamin D [ 53 ].…”
Section: Discussionmentioning
confidence: 99%